Risks of Ovarian, Breast, and Uterine Corpus Cancer in Women Receiving IVF Treatment (Sirte Journal of Medical Sciences, 2024)
Background A common treatment for infertility or genetic issues today is assisted reproductive technology (ART), which includes in vitro fertilization (IVF). Numerous studies have been done in this area in order to better understand the potential effects of this technique on women who undergo in vitro fertilization (IVF) and children born through IVF. This study is an updated meta-analysis to determine whether there is a causal relationship between different fertility treatments and ovarian, breast cancer. - Methods To reflect contemporary in vitro fertilization (IVF) practice, studies written during the last 20 years were included. Finding out whether women who receive hormonal reproductive treatment have an elevated risk of ovarian, breast cancer was the study's main objective. To find out if individual fertility therapies increased the risk of breast cancer, one of the secondary outcomes was to do so. Researcher observed first cancer diagnoses for ovarian, breast, and corpus uteri were compared to expected rates for each age, sex, and period. With the help of age, sex, and time-specific incidence rates, standardized incidence ratios (SIRs) were computed. Results On this subject, there are opposing viewpoints. According to some research, the risk of developing hormone-sensitive malignancies, such as ovarian, breast cancer, has somewhat increased. Breast cancer is one of the most common malignancies in women and the long-term use of IVF drugs can raise estrogen hormones and lead to excessive gene expression, increasing the risk of the disease.  Conclusion There are a few dangers to be aware of as a result of the theory that lengthy IVF treatments may cause breast cancer in IVF candidates. Additionally, ovarian, breast cancer risk may be elevated in women with a favorable family history and associated inherited genes. The likely effects of the reproductive therapy approaches should therefore be explained to women who are candidates for IVF. Explained to women who are candidates for IVF.